Evolutionary responses to global change in species‐rich communities. Issue 1 (22nd August 2019) - Lau, Jennifer A.; terHorst, Casey P.
Abstract: Evolution in nature occurs in the proverbial tangled bank. The species interactions characterizing this tangled bank can be strongly affected by global change and can also influence the fitness and selective effects of a global change on a focal population. As a result, species interactions can influence which traits will promote adaptation and the magnitude or direction of evolutionary responses to the global change. First, we provide a framework describing how species interactions may influence evolutionary responses to global change. Then, we highlight case studies that have explicitly manipulated both a global change and the presence or abundance of interacting species and used either experimental evolution or quantitative genetics approaches to test for the effects of species interactions on evolutionary responses to global change. Although still not frequently considered, we argue that species interactions commonly modulate the effects of global change on the evolution of plant and animal populations. As a result, predicting the evolutionary effects of the multitude of global changes facing natural populations requires both community ecology and evolutionary perspectives. Abstract : In this review, we focus on how the presence and/or abundance of interacting species (i.e., the community context) influences evolutionary effects of human‐caused global changes because (1) the global change alters the strength of species interactions and the strength of selection imposed by species interactions, or reciprocally (2) species interactions alter the strength of selection imposed directly by global change.